Soft memtransistor with ion transfer interface. (1st March 2022) - Zhang, Zhong-Da; Zhong, Ya-Nan; Xu, Jian-Long; Gao, Xu; Wang, Sui-Dong
Abstract: A paradigm for soft memtransistor is demonstrated based on the ion transfer interface, consisting of an ion-rich semiconducting polymer layer on the top and a gelatin dielectric for receiving ions on the bottom. The flexible polymer memtransistor acted as an analog-type memristor without gating, and its memristive strength could be largely modulated by applying gate voltage. It is proposed that the ion redistribution across the ion transfer interface can modify the hole doping level in the polymer layer, which is responsible for the tunable memristive characteristics. Different levels of synaptic potentiation and depression were successfully emulated using the polymer memtransistor, and it is promising to extend the emulation to multi-terminal heterosynaptic plasticity.